2021
DOI: 10.1080/09593330.2021.1992509
|View full text |Cite
|
Sign up to set email alerts
|

Treatment capacity of a novel flexible fibre biofilm bioreactor treating high-strength milk processing wastewater

Abstract: This study was focused on the capacity investigation of a novel multistage flexible fiber biofilm reactor (MS-FFBR) to treat milk processing wastewater (MPW) with high organic loading (OLR). The MS-FFBR performance was evaluated at four intermediate stages separately and also the final effluent quality of the overall system with an influent chemical oxygen demand (COD in ) ranged from 1500±20 to 6000±50 mg/L and hydraulic retention times (HRTs) of 8, 12, 16 h. By comparting the bioreactors into the four stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In another study, the maximum TCOD removal efficiency was obtained at an HRT of 12 h and COD in of 1590 mg/L [ 10 ]. The authors demonstrated that the increase in COD in led to the reduction in contribution of consecutive stages in TCOD removal efficiency [ 11 ]. In another study, effluent turbidity of 1 NTU was reported at HRTs of 4 and 8 h [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, the maximum TCOD removal efficiency was obtained at an HRT of 12 h and COD in of 1590 mg/L [ 10 ]. The authors demonstrated that the increase in COD in led to the reduction in contribution of consecutive stages in TCOD removal efficiency [ 11 ]. In another study, effluent turbidity of 1 NTU was reported at HRTs of 4 and 8 h [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, Yu et al developed FFBR into a two-stage flexible fibre biofilm reactor to treat food processing wastewater [ 9 ]. Total chemical oxygen demand (COD) removal efficiency was 97% at COD in of 2700 mg/L with an organic loading rate (OLR) of 7.7 kg/m 3 d. With the inspiration from this work, we designed an innovative sequencing batch flexible fibre biofilm reactor (SB-FFBR), flexible fibre biofilm bioreactor, and multistage flexible fibre biofilm reactor to remediate raw milk processing wastewater [ 10 , 11 , 12 , 13 ]. The COD and TSS removal efficiencies were reported to be 92.5% and 89.1%, respectively, showing the high performance of the biofilm reactor.…”
Section: Introductionmentioning
confidence: 99%